2009
DOI: 10.1016/j.joca.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of three semi-quantitative radiographic grading techniques for hip osteoarthritis in terms of validity and reproducibility in 1404 radiographs: report of the OARSI-OMERACT Task Force

Abstract: Categorical JSW has similar validity and higher sensitivity to change than the other categorical scoring techniques in hip OA. These results indicate categorical JSW may be the preferred method to evaluate structural severity in hip OA clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 18 publications
0
43
0
Order By: Relevance
“…Baseline and follow-up radiographs were graded as KL 0-no radiographic features of OA, 1-doubtful JSN, 2-definite osteophytes and possible JSN, 3-multiple osteophytes, definite JSN and sclerosis, and 4-large osteophytes, marked JSN, severe sclerosis and deformity [21]. Each radiograph was similarly graded on the basis of the OARSI JSN classification as none, mild, moderate, or severe (0-3, respectively) [22,23]. Progression in either KL or OARSI score was defined as any increase from baseline value.…”
Section: Image Acquisition/analysismentioning
confidence: 99%
“…Baseline and follow-up radiographs were graded as KL 0-no radiographic features of OA, 1-doubtful JSN, 2-definite osteophytes and possible JSN, 3-multiple osteophytes, definite JSN and sclerosis, and 4-large osteophytes, marked JSN, severe sclerosis and deformity [21]. Each radiograph was similarly graded on the basis of the OARSI JSN classification as none, mild, moderate, or severe (0-3, respectively) [22,23]. Progression in either KL or OARSI score was defined as any increase from baseline value.…”
Section: Image Acquisition/analysismentioning
confidence: 99%
“…The Croft grade had the weakest associations with clinical symptoms of hip OA [5] . Construct validity was assessed between the pain and function and X-ray stages in hip OA patients by Gossec et al They concluded that KL, OARSI stages and categorization of JSW all have similar predictive and construct validity, it appears that categorical JSW is more reproducible and more sensitive to change and may be the preferred method to evaluate structural severity in hip OA clinical trials [7] . As a conclusion the measurement of minimal joint space width (JSW) was generally acknowledged as the cardinal individual feature in assessment of radiological hip OA and for monitoring of progression of degeneration over time and correlate with clinical status of hip OA patients [16,17] .…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Most studies have used radiological changes to define hip OA [2,3] . Although there are various definitions of hip OA, cross-sectional association with symptoms which represent construct validity of these definitions has rarely been studied in hip OA and the results are conflicting [4][5][6][7] . Radiographic variables, particularly minimal joint space width measurement (JSW), are considered the most appropriate structural with Spearman correlation test.…”
Section: Introductionmentioning
confidence: 99%
“…When compared with the major categorical systems for hip osteoarthritis, such as the Kellgren and Lawrence [2] system and Osteoarthritis Research Society International stages [3], JSW showed higher sensitivity for advancement of osteoarthritis [4]. Recent advancement of MR imaging allows three-dimensional morphological measurement of hip articular cartilage directly [5,6].…”
Section: Introductionmentioning
confidence: 99%